2011
DOI: 10.1111/j.1759-8893.2011.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmaceutical drug information brochures in the Emirate of Abu Dhabi (United Arab Emirates)

Abstract: Objective  A major marketing tool used by pharmaceutical companies in the Emirate of Abu Dhabi in the United Arab Emirates is direct‐to‐healthcare professional marketing utilizing promotional drug information brochures. The aim was to investigate whether the information in promotional brochures presented to healthcare professionals in the Emirate of Abu Dhabi by pharmaceutical representatives complied with the US Food and Drug Administration (FDA) criteria for brochures. Methods  The Health Authority – Abu Dha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Drug reference books, advice from colleagues, and scientific papers/journals were reported as the frequently utilized drug information resources by physicians 7. The brochures of pharmaceutical companies was another common source of drug information for physicians; however, brochures lacking appropriate scientific evidence can also compromise patient safety 8. Physicians are the first point of contact in clinical care, and their acquaintance with evidence-based drug information promotes rational prescribing behaviors that eventually lead to a better patient outcome 7…”
Section: Introductionmentioning
confidence: 99%
“…Drug reference books, advice from colleagues, and scientific papers/journals were reported as the frequently utilized drug information resources by physicians 7. The brochures of pharmaceutical companies was another common source of drug information for physicians; however, brochures lacking appropriate scientific evidence can also compromise patient safety 8. Physicians are the first point of contact in clinical care, and their acquaintance with evidence-based drug information promotes rational prescribing behaviors that eventually lead to a better patient outcome 7…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have indicated that direct mail from pharmaceutical manufacturers was the most frequently used source of information by physicians [3], with neighboring countries such as Saudi Arabia [5] and the United Arab Emirates being no exceptions as these are a major source of information for physicians [6], since access to full text journal articles and access to resources is limited in these countries [1]. Reliance on these sources of information is problematic as these sources are commercially-oriented and make the information suspect [1].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative advertising with another product is not permitted. The use of healthcare professionals for medical or drug advertising and advertising directed at children are not allowed [ 29 ]. India In India , pharmaceutical advertising includes any notice, circular, label, package, or other documents, as well as any notice produced or transmitted orally or by light, sound, or smoke.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative advertising with another product is not permitted. The use of healthcare professionals for medical or drug advertising and advertising directed at children are not allowed [29].…”
Section: Snapshot Of the National And International Regulations On Ph...mentioning
confidence: 99%